MODIFIKASI MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) DENGAN MODEL PEMBELAJARAN EXPLICIT INTRUCTION (EI) DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA - Taufan Asfar, A.M.Irfan; Akbar Asfar, A.M.Iqbal Akbar Asfar; Sartina, Sartina (EDUTECH CONSULTANT, 2018)
In reality, in the process of learning mathematics there are deficiencies in the practical context, among others, students are still just listening, watching, taking notes, then doing exercise questions and being passive. In overcoming the problems that occur requires a learning model that can accommodate several aspects to achieve learning goals. Various learning models are applied and still have some weaknesses so that this study has a purpose to present a learning model that covers the weaknesses of the model that has been applied which is useful to improve students' understanding of concepts in mathematics learning. Missouri Explicit Mathematics Instruction (EMMI) explicit model is the result of modification of the Missouri Mathematics Project (MMP) learning model with Explicit Instruction (EI) learning model. The EMMI learning model emphasizes various interactions between teachers and students, students and students, even with media and learning resources that enable students to learn basic skills and obtain information that can be taught step by step, in addition to collaborative learning the EMMI model also emphasizes student independence. The results showed that the EMMI model results for pretest t count of 4.869 and t table of 1.980 with a significant level of α = 0.05 in the rejection area of ​​H0, it was concluded that the implementation of Explicit Missouri Mathematics Instruction (EMMI) learning model could improve students' understanding of concepts.